A genome-wide association meta-analysis on lipoprotein (a) concentrations adjusted for apolipoprotein (a) isoforms - Mack S; Coassin S; Rueedi R; Yousri NA; Seppala I; Gieger C; Schonherr S; Forer L; Erhart G; Marques-Vidal P; Ried JS; Waeber G; et al. (AMER SOC BIOCHEMISTRY MOLECULAR BIOLOGY INC, 2022)
High lipoprotein (a) [Lp(a)] concentrations are an independent risk factor for cardiovascular outcomes. Concentrations are strongly influenced by apo(a) kringle IV repeat isoforms. We aimed to identify genetic loci associated with Lp(a) concentrations using data from five genome- wide association studies (n = 13,781). We identified 48 independent SNPs in the LPA and 1 SNP in the APOE gene region to be significantly associated with Lp(a) concentrations. We also adjusted for apo(a) isoforms to identify loci affecting Lp(a) levels independently from them, which resulted in 31 SNPs (30 in the LPA, 1 in the APOE gene region). Seven